Respiratory effects among non smoking women in relation to household cooking fuel uses: liquefied petroleum gas only, coal only and both liquefied petroleum gas and coal in Tu Liem Suburban District Hanoi Vietnam - Nguyen Thi My Hanh (Chulalongkorn University, 2014)
Thesis (M.P.H.)--Chulalongkorn University, 2012